Identification Of Bovine Papilloma Virus By Electron Microscopy In Cattle- A Case Report - Sathiyabama , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Papilloma Virus an epitheliotropic double stranded DNA virus, is a member of the family papillomaviridae, which is more commonly affecting cattle and also found infecting the human beings. The virus has been implicated as a cause for cancer and mortality (Campo,2003) when it is associated with many other factors. It develops cutaneous papillomatosis and benign proliferative lesions in cattle, therefore leads to severe economic impacts (Jelinek and Tachezy, 2005 and Boiron et al., 1965), Animals of less than two years old are highly susceptible to the infection and affected animals may recover in a month or an year, due to spontaneous healing nature of the virus.